Antiglycating Effect of Phenolics from the Chilean Currant Ribes cucullatum under Thermal Treatment - Felipe Ávila; Natalia Ravello; Camila Manriquez; Felipe Jiménez-Aspee; Guillermo Schmeda-Hirschmann; Cristina Theoduloz (MDPI AG, 2021)
Numerous dietary polyphenols possess antiglicating activity, but the effects of thermal treatment on this activity are mostly unknown. The effect of thermal treatment in the antiglycating activity of polyphenolic enriched extracts (PEEs) from Ribes cucullatum towards glyoxal-induced glycation of sarcoplasmic proteins was assessed. Sarcoplasmic proteins from chicken, beef, salmon, and turkey, were incubated 2 h at 60 °C with and without glyoxal and different concentrations of PEEs (0.25, 0.5, 1, and 5 mg/mL). The antiglycating activity was evaluated by: (1) Lys and Arg consumption, (2) Carboxymethyl lysine (CML) generation, and (3) lipid-derived electrophiles inhibition in a gastric digestion model. Protective effects were observed against CML generation in proteins and a decrease of electrophiles in the gastric digestion model. A dose-dependent consumption of Lys and Arg in proteins/PEEs samples, indicated the possible occurrence of quinoproteins generation from the phenolics. Protein/PEEs incubations were assessed by: (1) High pressure liquid chromatography analysis, (2) Gel electrophoresis (SDS-PAGE), and (3) Redox cycling staining of quinoproteins. Protein/PEEs incubations produced: (1) Decrease in phenolics, (2) increase of protein crosslinking, and (3) dose-dependent generation of quinoproteins. We demonstrate that phenolic compounds from R. cucullatum under thermal treatment act as antiglycating agents, but oxidative reactions occurs at high concentrations, generating protein crosslinking and quinoproteins.